Estimating Genetic Parameter of Saanen Goat Production Characteristics Using Paternal Half Sib Correlation - Irawati, Nurreni; Purwantini, Dattadewi; Sodiq, Akhmad (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
This research was aimed to investigate heritability score (h2) of milk yield, kid birth weight, and milk quality that included density, fat content, protein, lactose, water and non-fat dry matter of Saanen goat according to the production record of first-lactating individual in the Centre of Pedigree Breeding and Cattle Forage Baturraden. The materials for this research were 180 Saanen does with a first-lactating record. The estimated genetic parameter was heritability score using a paternal half-sib correlation method. Result showed that the heritability of milk yield, kid birth weight, density, fat content, protein, lactose, water and NFDM was 0,32+0,23; 0,25+0,26; 0,15+0,17; 0,11+0,16; 0,12+0,16; 0,10+0,14; 0,10+0,16 and 0,11+0,16, respectively. A high h2 was obtained from heritability score of milk yield, and a moderate h2 was from kid birth weight and milk quality. In conclusion, the h2 score of milk yield of Saanen goats was relatively high, while the h2 score of kid birth weight and milk quality was relatively moderate.